Differential sensitization of silent nociceptors to low pH stimulation by prostaglandin E2 in human volunteers. (30th May 2014) - Namer, B.; Schick, M.; Kleggetveit, I.P.; Ørstavik, K.; Schmidt, R.; Jorum, E.; Torebjörk, E.; Handwerker, H.; Schmelz, M.
Abstract Background Inflammatory mediators activate and sensitize nociceptors. Tissue acidosis with low pH of 5.5 often accompanies inflammation and could enhance inflammatory pain and sensitization. Methods Action potentials from single mechano‐responsive (CM) and mechano‐insensitive (CMi) C‐nociceptors of cutaneous fascicles of the peroneal nerve in healthy volunteers were recorded by microneurography. Low pH solutions with and without prostaglandin E2 (PGE2) were injected twice (with an interval of approximately 5 min) into two spots of the receptive fields of C‐fibres. Heat thresholds of the C‐fibres were obtained before and after each injection. Results Injections of the low pH solutions immediately induced phasic responses in CM nociceptors, whereas CMi fibres responded after a delay of several seconds with a sustained response. More CMi fibres than CM fibres showed ongoing discharge after low pH injection, but the duration and intensity of the responses to the first low pH injection did not differ between them. Upon repetition, duration and intensity of the pH responses increased more than twofold in CMi fibres only. Furthermore, combined application of pH and PGE2 sensitized the response in CMi fibres only. In contrast, heat activation thresholds were sensitized by the combination of low pH and PGE2 in both fibre classes. Conclusions Our results confirm nociceptor class independent heat sensitization by PGE2 which is probably mediated by transient receptor potential vanilloid 1 phosphorylation. However, prolonged and increased pain responses in humans upon low pH/PGE2 stimulation appear to be primarily dependent on CMi fibres, whereas CM nociceptors appear crucial for phasic responses.